Identification of biogenic sulphate corrosion of concrete in sewage treatment plant settling tank walls - Krysiak, Łukasz; Falaciński, Paweł; Szarek, Łukasz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
One of the basic threats in terms of concrete used for tanks or ducts applied in wastewater management is the phenomenon of biogenic sulphate corrosion (BSC). BSC is a particular case of corrosion caused by the action of sulphuric acid (IV), which is formed as a result of a number of biochemical processes, which can take place, e.g. in an environment encountered within the aforementioned structures.
Keywords: corrosion of concrete; sulphate corrosion; wastewater management; environmental protection; case study; korozja betonu; korozja siarczanowa; gospodarka ściekowa; ochrona środowiska; studium przypadku